2008
DOI: 10.1167/iovs.08-1980
|View full text |Cite
|
Sign up to set email alerts
|

Scleral Hydraulic Conductivity and Macromolecular Diffusion in Patients with Uveal Effusion Syndrome

Abstract: UES is not caused by reduced scleral hydraulic conductivity, which tends to be higher than expected. Reduced macromolecular diffusion may impede the normal transscleral egress of albumin with subsequent osmotic fluid retention in some, but not all eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 15 publications
0
38
1
2
Order By: Relevance
“…Indeed, ciliochoroidal effusion can be the consequence of various inflammatory and hydrostatic ocular conditions. In eyes affected by idiopathic UES, a primary abnormality of the sclera may play a causal role in the dysfunction of choroidal fluid dynamics [12]. Histochemical studies have shown an accumulation of glycosaminoglycan-like deposits filling the interfibrillar spaces in sclera excised from eyes affected by UES [13][14][15][16].These alterations are associated with the abnormal transscleral diffusion of choroidal extravascular proteins and the accumulation of fluid in the choroid as a result of increased osmolarity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, ciliochoroidal effusion can be the consequence of various inflammatory and hydrostatic ocular conditions. In eyes affected by idiopathic UES, a primary abnormality of the sclera may play a causal role in the dysfunction of choroidal fluid dynamics [12]. Histochemical studies have shown an accumulation of glycosaminoglycan-like deposits filling the interfibrillar spaces in sclera excised from eyes affected by UES [13][14][15][16].These alterations are associated with the abnormal transscleral diffusion of choroidal extravascular proteins and the accumulation of fluid in the choroid as a result of increased osmolarity.…”
Section: Discussionmentioning
confidence: 99%
“…MFRP mutations may also cause retinitis pigmentosa or foveoschisis [5] and it is possible that a malfunction of the gene itself may contribute to UES. Indeed, a recent laboratory study of specimens excised from nanophthalmos patients with UES found the scleral hydraulic conductance to be in the normal range [6].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Medical treatment using NSAIDs has been described with rare success. 8 PAs are known to enhance scleral macromolecular permeability.…”
Section: Discussionmentioning
confidence: 99%